Delaying sexual onset: outcome of a comprehensive sexuality education initiative for adolescents in public schools - Dolores Ramírez-Villalobos; Eric Alejandro Monterubio-Flores; Tonatiuh Tomás Gonzalez-Vazquez; Juan Francisco Molina-Rodríguez; Ma. Guadalupe Ruelas-González; Jacqueline Elizabeth Alcalde-Rabanal (BMC, 2021)
Abstract Background A common risk behavior in adolescence is the early initiation of unprotected sex that exposes adolescents to an unplanned pregnancy or sexually transmitted infections. Schools are an ideal place to strengthen adolescents' sexual knowledge and modify their behavior, guiding them to exercise responsible sexuality. The purpose of this article was to evaluate the knowledge of public secondary school teachers who received training in comprehensive education in sexuality (CES) and estimate the counseling's effect on students' sexual behavior. Methods Seventy-five public school teachers were trained in participatory and innovative techniques for CES. The change in teacher knowledge (n = 75) was assessed before and after the training using t-tests, Wilcoxon ranks tests and a Generalized Estimate Equation model. The students' sexual and reproductive behavior was evaluated in intervention (n = 650) and comparison schools (n = 555). We fit a logistic regression model using the students' sexual debut as a dependent variable. Results Teachers increased their knowledge of sexuality after training from 5.3 to 6.1 (p < 0.01). 83.3% of students in the intervention school reported using a contraceptive method in their last sexual relation, while 58.3% did so in the comparison schools. The students in comparison schools were 4.7 (p < 0.01) times more likely to start sexual initiation than students in the intervention schools. Conclusion Training in CES improved teachers' knowledge about sexual and reproductive health. Students who received counseling from teachers who were trained in participatory and innovative techniques for CES used more contraceptive protection and delayed sexual debut.